LianChuang ZhiXue Liquid Enema Modulates the Macrophage Polarization of Ulcerative Colitis via Inhibiting the Jagged-1/Notch1 Signaling Pathway - Zhang Y; Liu J; Zhang D; Qian H (Drug Design, Development and Therapy)
Yongli Zhang,1,2,* Jiali Liu,1,* Dan Zhang,1 Haihua Qian1 1Department of Anorectal Surgery, Affiliated Hospital of Nanjing University of Chinese Medicine, Nanjing, Jiangsu, 210029, People’s Republic of China; 2Department of Anorectal Surgery, Xi’an Hospital of Traditional Chinese Medicine, Xi’an, Shaanxi, 710016, People’s Republic of China*These authors contributed equally to this workCorrespondence: Dan Zhang, Department of Anorectal Surgery, Affiliated Hospital of Nanjing University of Chinese Medicine, Qinhuai Road, No. 155, Nanjing, Jiangsu, 210029, People’s Republic of China, Email danaezhang@163.com Haihua Qian, Department of Anorectal Surgery, Affiliated Hospital of Nanjing University of Chinese Medicine, Qinhuai Road, No. 155, Nanjing, Jiangsu, 210029, People’s Republic of China, Email qianhaihua_nzy@126.comObjective: LianChuang ZhiXue Liquid (LCZXL) enema, one of the classic Chinese medicine prescriptions, in which herbal decoction enema acts directly on the intestines, is clinically effective in patients with ulcerative colitis (UC). However, its specific molecular mechanism has not been clarified to explore the underlying macular mechanism of LCZXL enema effect on UC, based on Jagged-1/Notch1 signaling pathway and the macrophage polarization.Methods: After modeling of UC mice, the experiment was conducted in two parts: Experiment I: Control, Model, Mesalazine, Low dose of LCZXL (LCZXL-L), High dose of LCZXL (LCZXL-H); Weight and Disease Activity Index (DAI) scores were recorded on days 1, 3, 5, 7, 9, 11, and 13. On day 14, the colon was taken off. Then the colon length was measured and the damage index (CMDI) score of colon mucosal was evaluated. Zonula occludens-1 (Zo-1) Immunohistochemistry (IHC) and Hematoxylin-Eosin (HE) staining were performed to visualize the colon injury. ELISA was used to detect cytokines content in serum. The M1 and M2 markers and Jagged-1/Notch1 signaling pathway-related genes/proteins were quantified by IF double staining, PCR, WB, and flow cytometry. Experiment II: Control, Model, Recombinant mouse Jagged-1 protein/ Fc Chimera Active (Jagged-1/Fc), LCZXL, Jagged-1/Fc+LCZXL. The M1 and M2 markers and Jagged-1 proteins were quantified by WB, and flow cytometry.Results: Our results indicated that LCZXL could reduce the colon injury of UC mice effectively, which expressed DAI and CMDI score reduction, and inhibited colon structure damage. DSS induced a significant up-regulation of CD86, iNOS, TNF-α, IL-1β, and IL-6, and a down-regulation of Arg1, CD206, IL-4, IL-10 and increase of Jagged-1, Notch1, and Notch2. LCZXL enema treatment inhibiting the increase of UC modeling-induced CD86, TNF-α, IL-1β, and IL-6 and increased CD206, Arg1, IL-4, and IL-10 expression level. Notch signaling pathway activator Jagged-1/Fc aggravated M1 macrophage polarization and activated the Jagged-1/Notch1 signaling pathway. LCZXL treatment reversed this situation stop the activation of the Jagged-1/Notch1 signaling pathway.Conclusion: Our study proved that LCZXL Enema could inhibit the M1 Macrophage Polarization and promote M2 macrophage polarization of ulcerative colitis via regulating the Jagged-1/Notch1 signaling pathway. Keywords: LCZXL enema, M2 macrophage polarization, ulcerative colitis, Jagged-1/Notch1 signaling pathway